2014
DOI: 10.1038/nature12995
|View full text |Cite
|
Sign up to set email alerts
|

The remnant of a merger between two dwarf galaxies in Andromeda II

Abstract: Driven by gravity, massive structures like galaxies and clusters of galaxies are believed to grow continuously through hierarchical merging and accretion of smaller systems. Observational evidence of accretion events is provided by the coherent stellar streams crossing the outer haloes of massive galaxies, such as the Milky Way 1 or Andromeda 2 . At similar mass-scales, around 10 11 solar masses in stars, further observational evidence of merging activity is also ample 3,4,5 . Mergers of lower-mass galaxies ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 28 publications
5
112
0
Order By: Relevance
“…These gradients are particularly clear in some galaxies and, when accompanied by correlated differences in kinematics and metallicity, are often interpreted as evidence for distinct stellar components. The Sculptor dSph makes a compelling example of a system with at least two distinct components (Tolstoy et al 2004;Battaglia et al 2008), but so do other dwarfs such as Sextans (Battaglia et al 2011); the And II companion to M31 (McConnachie et al 2007;Amorisco et al 2014); and Fornax (Battaglia et al 2006;Walker & Peñarrubia 2011). We note, however, that clear-cut evidence for distinct components is often weak, and that these may also be interpreted as simply cases where the radial gradients are particularly pronounced.…”
Section: Introductionmentioning
confidence: 73%
“…These gradients are particularly clear in some galaxies and, when accompanied by correlated differences in kinematics and metallicity, are often interpreted as evidence for distinct stellar components. The Sculptor dSph makes a compelling example of a system with at least two distinct components (Tolstoy et al 2004;Battaglia et al 2008), but so do other dwarfs such as Sextans (Battaglia et al 2011); the And II companion to M31 (McConnachie et al 2007;Amorisco et al 2014); and Fornax (Battaglia et al 2006;Walker & Peñarrubia 2011). We note, however, that clear-cut evidence for distinct components is often weak, and that these may also be interpreted as simply cases where the radial gradients are particularly pronounced.…”
Section: Introductionmentioning
confidence: 73%
“…This formation scenario was suggested in order to explain the prolate rotation that was recently observed in the dwarf spheroidal galaxy Andromeda II (Ho et al 2012), the first dwarf galaxy observed to show such a feature in the form of a stellar stream rotating around its major projected axis (see also Kacharov et al 2017, for their recent discovery of prolate rotation in another dwarf galaxy). This feature in Andromeda II was interpreted as evidence of a past major merger between two dwarf galaxies (Amorisco et al 2014).…”
Section: Summary and Discussionmentioning
confidence: 96%
“…Such haloes retain a fossil record of past mergers and interactions in the form of extended tidal debris (e.g. Searle & Zinn 1978;Martínez-Delgado et al 2001;Muñoz et al 2006;Sohn et al 2007;Amorisco, Evans & van de Ven 2014).…”
Section: Introductionmentioning
confidence: 99%